Penentuan keputusan dalam proses perancangan dan perlaksanaan projek / Faridah Mohamad Yusoff - Faridah, Mohamad Yusoff (Faculty of Architecture, Planning & Surveying, 1983)
As every experienced executive knows, a major part of a manager's time is occupied in a daily process of making numerous and diverse decisions. The demands on the decision maker's time always seem to exceed his capacity, decisions of great potential import come mixed with trivial but time consuming demands. This diversity generally tends to increase with the level of responsibility and becomes particularly pronounced for the top executive of the firm. On a single day he may be called upon to decide on a future course of the firm's business to reconcile on organizational conflict between two executive, and to resolve a host of day to day operating problems.